2022
DOI: 10.3390/curroncol29050267
|View full text |Cite
|
Sign up to set email alerts
|

Primary Angiosarcoma of the Breast: A Single-Center Retrospective Study in Korea

Abstract: Due to the rarity of primary angiosarcoma of the breast, optimal management is based on expert opinion. The aim of this study was to review all primary angiosarcomas of the breast obtained from a single center in terms of clinicopathologic characteristics, treatment, and survival outcomes. From 1997 to 2020, 15 patients with primary angiosarcoma of the breast underwent either mastectomy or wide excision. We analyzed the clinicopathologic data to assess disease-free survival and overall survival. Fifteen women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Studies show that larger tumour size and higher grade are associated with an increased risk of local recurrence and reduced overall survival. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Studies show that larger tumour size and higher grade are associated with an increased risk of local recurrence and reduced overall survival. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is the primary treatment for angiosarcoma of the breast, which often involves mastectomy with the removal of all irradiated tissue [5]. However, angiosarcoma can present as a multifocal lesion, so it can be challenging to achieve complete resection with clear margins.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of PBA is very poor, and patients undergoing surgery at the earliest may prolong the life ( 9 ). Abdou concluded that tumor size and grade are reliable predictors of prognosis, and survival is significantly lower for high-grade tumors or those spanning greater than 5 cm ( 3 , 10 ). However, Alessandra concluded that grade does not affect prognosis ( 11 ).…”
Section: Discussionmentioning
confidence: 99%